Does Public Policy Affect Attitudes? Evidence from Age-Based Health Insurance Coverage Policies in the United States - Baris Yörük (Institute of Labor Economics (IZA), 2022)
The existing literature provides evidence that public opinion and attitudes often affect public policy. However, little is known on how public policy might affect public attitudes and norms. I present new evidence on this topic by using age-based health insurance policies in the United States as natural experiments. I first exploit the discrete change in insurance coverage rates at age 26 due to the Affordable Care Act's dependent coverage mandate and show that this policy is associated with statistically significant deterioration in attitudes towards the necessity of health insurance among young adults who are affected by this policy the most. Next, I show that gaining health insurance at 65 due to the onset of Medicare does not have a significant impact on attitudes towards health insurance among the elderly. These findings are widespread across different demographic groups, robust under alternative model specifications, observed only after the policies are adopted, and highlight the importance of age in attitude formation.
Keywords: I12; I13; I18; 330; attitudes; beliefs; health insurance coverage; public policy